2016
DOI: 10.1002/2016jd025115
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns and source implications of aromatic hydrocarbons at six rural sites across China's developed coastal regions

Abstract: Aromatic hydrocarbons are important anthropogenic precursors of tropospheric ozone and secondary organic aerosols. Here we measured ambient aromatic hydrocarbons from March 2012 to February 2014 at six rural sites in China's developed coastal regions. On average, benzene (B) comprised > 50% of total benzene (B), toluene (T), ethylbenzene (E), and xylenes (X) (BTEX) at sites in the Northeast China Plain (NECP) or in the North China Plain (NCP), whereas T, E, and X accounted for > 77% of total BTEX at sites in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(43 citation statements)
references
References 96 publications
1
41
1
Order By: Relevance
“…It is worth noting that recent chamber studies revealed that aromatic hydrocarbons and traditional VOCs could not fully explain the SOA formed during atmospheric aging of source emissions (Zhao et al, 2014(Zhao et al, , 2015Deng et al, 2017;Fang et al, 2017), particularly for emissions from diesel vehicles or biomass burning (Zhao et al, 2015;Deng et al, 2017;Fang et al, 2017). Therefore the discussion on the SOAFP in this study is limited to traditional anthropogenic SOA precursor species (mainly aromatic hydrocarbons), and intermediate-volatility organic compounds (IVOCs), which are important SOA precursors (Zhao et al, 2014), should be further considered in order to fully understand the influence of control measures on ambient SOA.…”
Section: Source Contributions To the Soafpmentioning
confidence: 99%
“…It is worth noting that recent chamber studies revealed that aromatic hydrocarbons and traditional VOCs could not fully explain the SOA formed during atmospheric aging of source emissions (Zhao et al, 2014(Zhao et al, , 2015Deng et al, 2017;Fang et al, 2017), particularly for emissions from diesel vehicles or biomass burning (Zhao et al, 2015;Deng et al, 2017;Fang et al, 2017). Therefore the discussion on the SOAFP in this study is limited to traditional anthropogenic SOA precursor species (mainly aromatic hydrocarbons), and intermediate-volatility organic compounds (IVOCs), which are important SOA precursors (Zhao et al, 2014), should be further considered in order to fully understand the influence of control measures on ambient SOA.…”
Section: Source Contributions To the Soafpmentioning
confidence: 99%
“…Toluene is the most abundant aromatic hydrocarbon (Calvert et al, 2002;Zhang et al, 2016), and SOA yields from the photooxidation of toluene on dry or wet ammonium sulfate (AS) seeds have been studied by varying the RH in smog chambers. Kamens et al (2011) observed higher yields of SOA from toluene at higher RHs.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) in the ambient air samples were also analyzed with an Agilent model 6890 gas chromatography equipped with a FID and a packed column (5Å Molecular Sieve 60/80 mesh, 3 m1/8 inch). CO was first separated by packed column, then converted to CH4 by Ni-based catalyst and finally detected by FID (Zhang et al, 2016a).…”
Section: Sampling Site and Field Samplingmentioning
confidence: 99%
“…previous study demonstrated that levels of aromatic hydrocarbons and carbonyls increased significantly under haze days in urban Beijing from 2008 to 2010 (Zhang et al, 2014b), yet few reports are available about wintertime precursor VOCs in Beijing. In urban areas, vehicle exhausts are important sources of SOA precursors (McDonald et al, 2015;Liu et al, 2015a;Ortega et al, 2016;Deng et al, 2017;Gentner et al, 2017). However, biomass/biofuel burning and coal burning may also contribute substantially to SOA precursors (Yokelson et al, 2008;Shrivastava et al, 2015;Fang et al, 2017), particularly in north China in wintertime when raw coal and biofuels are widely used for household heating (Liu et al, 2016;Zhang et al, 2016a;. In fact, a study by in 2011-2012 revealed that even at an urban site in Beijing coal combustion could account for 28-39% of VOCs observed in ambient air.…”
Section: Introductionmentioning
confidence: 99%